Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/6662344
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the EP and Anti-PD-1 Pathway or Anti-CTLA-4 for the Phase III Trial of Small-Cell Lung Cancer: A Meta-Analysis

Abstract: The morbidity and mortality of lung cancer remain one of the highest among multiple cancers, respectively. Small-Cell Lung Cancer (SCLC) accounts for around 10%–15% of all lung cancers. Approximately two-thirds of the diagnosed SCLCs are in extensive stage (ES). Decades later, we still rely on the same traditional regimen with etoposide and platinum (EP) as the mainstay of treatment with poor prognosis. This meta-analysis aims to assess the effect of adding Immune Checkpoint Inhibitors (CPIs) such as (ipilimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…SCLC, with its high tumor mutational burden, is notably responsive to immunotherapy [17,18]. Multiple trials have substantiated the survival benefits of blocking the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed death 1 (PD-1), and programmed death ligand 1 (PD-L1) axis, either in conjunction with chemotherapy or as maintenance therapy, for ES-SCLC patients [19][20][21]. However, several studies indicated that immunotherapy did not improve OS and PFS of ES-SCLC patients with liver metastases [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…SCLC, with its high tumor mutational burden, is notably responsive to immunotherapy [17,18]. Multiple trials have substantiated the survival benefits of blocking the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed death 1 (PD-1), and programmed death ligand 1 (PD-L1) axis, either in conjunction with chemotherapy or as maintenance therapy, for ES-SCLC patients [19][20][21]. However, several studies indicated that immunotherapy did not improve OS and PFS of ES-SCLC patients with liver metastases [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Past studies showed that treatment with anti-CTLA-4 mab alone did not have a significant effect on the prognosis of lung cancer, which is why most recent investigations focus on combining CTLA-4 inhibition therapy with either other ICIs, or traditional regimens (e.g., etoposide and platinum chemotherapies) in SCLC and NSCLC [ 63 ]. A preclinical mouse trial, conducted by Bates et al., for example, indicates anti-CTLA-4 as a possible adjunct to bempegaldesleukin (a CD122-preferential IL-2 pathway agonist), as a secondary treatment after surgical resection or hypo-fractionated radiation therapy of primary Lewis Lung Carcinoma (LLC), a specific type of NSCLC.…”
Section: Existing and Novel Immune Checkpoint Inhibition (Ici) Therapiesmentioning
confidence: 99%